Elektrische Klangmaschinen - Donhauser, Peter (2007)
The publication deals with the time of pioneers in building "electrical musical instruments" in German speaking countries. It is based on a research project funded by the Austrian National Bank's "Jubilaeumsfonds" (project number 9382), where the popularisation of these instruments was in focus. Starting with the first attempts the development in the respective region is examined for the time between 1920 and 1945 using carefully investigated documents. After a short description of the roots going back to the 19th century the documentation continues with a critical evaluation of the constructions and their presentation in the 1920ties (especially Joerg Mager and Lev Termen and the reaction of experts and the public). Electro-optic and electromagnetic sound generation was invented in that time as well but appeared later on. There are examples for both principles in Austria and Germany reaching back to the 1920ties. A representative survey of press reports show the different estimations of the usability of electrical musical instruments by technicians, musicians and the public. The following decade is treated in several parts due to the political development in Germany. The first two years are mainly marked by the invention of the Trautonium, the Neo-Bechstein-piano, the Elektrochord and the Hellertion. This was the time when Berlin turned out as a centre for "electrical music", especially by activities of the "Rundfunkversuchsstelle" (radio research institute) at the University of Music and the Heinrich-Hertz-Institute. The first major public presentations at the Berlin Radio Shows took place in this time as well. After the year 1933 not only the political situation changed but the cultural preconditions for the usage of electrical instruments as well. The political convergence with the NS regime and the goodwill of the "ministry of public enlightenment and propaganda" played an important role. It turned out by the following development that the Trautonium, the electric organs by Vierling and the Hellertion by Bruno Helberger were used for official occasions. Vierling's "Grosstonorgel" was used during the Olympic games, on the other hand the development of Edwin Welte's light-tone organ was stopped for he was married with a Jewish woman. The work of Oskar Sala plays an important role in the area of conflict between technology, politics and music. As no detailed documentation of the work of Joerg Mager (who claimed to be the leading person in electro-music research) is available till now, this will be discussed in a separate chapter. A short description of the consequences after 1945 is followed by a detailed appendix: data of concerts, sound recordings, technical documentations and more than 600 patents. The book is based on extensive and original material, as it turned out by studying of secondary literature that many details are based on not provable sources. The facts are carefully documented using footnotes, the book is meant as a fundamental collection of sources for further scientific research. Die Publikation handelt von der Pionierzeit der "elektrischen Instrumente" im deutschsprachigen Raum. Sie beruht im Wesentlichen auf einem Forschungsauftrag des Jubiläumsfonds der Österreichischen Nationalbank (Projekt Nr. 9382), bei dem vor allem die Popularisierung dieser Instrumente im Vordergrund stand. Von den ersten Versuchen ausgehend, wird anhand von sorgfältig recherchierten Originaldokumenten die Entwicklung im untersuchten geographischen Raum vorzugsweise im Zeitintervall von 1920 bis 1945 behandelt. Nach einer kurzen Darstellung der ins 19. Jh. zurückreichenden Wurzeln beginnt die Untersuchung mit einer kritischen Wertung der Konstruktionen und deren Präsentation in den 1920er Jahren (insbesondere Jörg Mager, Lev Termen und den Reaktionen der Fachwelt und der Öffentlichkeit). Dazu kommen Konstruktionen, die zwar in dieser Zeit entstanden, jedoch erst später in Erscheinung traten: die elektro-optische und elektromagnetische Tonerzeugung. Für beide Prinzipien gibt es Beispiele in Österreich und Deutschland, die in die 1920er Jahre zurückreichen. Eine repräsentative Presseschau zeigt die unterschiedliche Auffassung der Verwertbarkeit der elektrischen Instrumente vom Standpunkt der Techniker, der Musiker und der Öffentlichkeit. Das folgende Jahrzehnt wird der politischen Entwicklung wegen in mehreren Teilen behandelt. Die ersten zwei Jahre waren vor allem von der Erfindung des Trautoniums, des Neo-Bechstein-Flügels, des Elektrochords und des Hellertions geprägt. In dieser Zeit entwickelte sich Berlin (insbesondere durch das Heinrich Hertz Institut und die Rundfunkversuchsstelle) zu einem Zentrum der "elektrischen Musik". Auch die ersten großen öffentlichen Präsentationen auf den Berliner Funkausstellungen fanden 1931 und 1932 statt. Nach 1933 veränderte sich jedoch nicht nur die politische Lage, sondern auch die kulturpolitischen Voraussetzungen für die Verwendung elektrischer Instrumente. Die politische Nähe zum NS Regime und das Wohlwollen des Propagandaministeriums spielten eine wesentliche Rolle. Die Entwicklung zeigte, dass das Trautonium, die Orgelkonstruktionen von Oskar Vierling und das Hellertion Bruno Helbergers im offiziellen Musikbetrieb weiter verwendet wurden. Vierlings "Großtonorgel" wurde bei offiziellen Anlässen eingesetzt, hingegen wurde die Entwicklung der Lichttonorgel Edwin Weltes gestoppt, weil er mit einer Jüdin verheiratet war. Oskar Salas Arbeit spielt im Spannungsfeld zwischen Technik, Politik und Musik eine wichtige Rolle. Nachdem bislang keine ausführliche Dokumentation der Arbeit Jörg Magers (der für sich eine besondere Rolle in Anspruch nahm) verfügbar war, ist diesem Thema ein eigenes Kapitel gewidmet. Einer kurzen Darstellung der Folgewirkungen nach 1945 folgt ein ausführlicher Anhang, der das ermittelte Material offenlegt: Aufführungsdaten, Tondokumente, technische Dokumentationen und über 600 Patente werden aufgelistet. Die Arbeit beruht auf umfangreichem Originalmaterial, da es sich beim Studium der Sekundärliteratur zeigte, dass viele Details auf nicht weiter nachvollziehbaren Quellen beruhen. Die Fakten sind sorgfältig in Fußnoten dokumentiert, das Buch versteht sich daher auch als grundlegende Quellensammlung für weiterführende wissenschaftliche Arbeit.